Investigation of energy and mass balance “Trimyx-3M” Galatea multipole magnetic trap - Bishaev, A.M.; Bugrova, A.I.; Kozintseva, M.V.; Lipatov, A.S.; Savelyev, V.V.; Sigov, A.S.; Tarelkin, I.A.; Terekhov, V.A.; Desyatskov, A.V. (Вопросы атомной науки и техники, 2011)
In the work using Rogowski loop, measurements of the diamagnetic current, generating in the plasma volume of the “Trimyx-3M” Galatea multipole magnetic trap under its filling by plasmoids have been carried out. These measurements are confirmed by signals from diamagnetic probes. The mean value of the energy in plasma volume in the process of the trap filling by plasma and during plasma decay have been determined by the magnitude of diamagnetic current. These measurements are carried out simultaneously with the measurement of the time dependence of mean plasma density by microwave interferometer.